PENGARUH ROLE STRESS, EMOTIONAL INTELLIGENCE, DAN ASPEK PSYCHOLOGICAL WELL-BEING TERHADAP KINERJA AUDITOR - Hendi Prasetyo; Tatik Zulaika; Maureen Marsenn (Balance: Media Informasi Akuntansi dan Keuangan, 2023)
The purpose of this study was to examine Role Stress, Emotional Intelligence, and Psychological Well-Being Aspects on Auditor Performance at BPK KalTeng. The data used in this study are primary data. Respondents in this study were 68 employees. The method of collecting data in this study using a questionnaire. This research shows that Role Stress, Emotional Intelligence, and Psychological Well-Being Aspects have an effect on Auditor Performance.